The personality traits of Polish junior and senior national team in Olympic karate and handball - comparative analysis - Piepiora, P.; Reguli, Z.; Witkowski, K.; Maœliñski, J.; Dzióba, N.; Piepiora, Z. (Archives of Budo, 2022)
Background and Study Aim: Research on personality in sport often concerns the senior stage, that is why we are interested in the junior stage. The aim of this research is the personal profiles of athletes training combat sport and team sport at the level of the Polish representation of juniors and seniors. Material and Methods: The subjects of the study were members of the Polish junior and senior national teams in Olympic karate (n = 41) and handball (n = 39) from the 2020/2021 season. We based our comparative analysis on the Five-Factor Model of Personality, known as the Big Five, was used to measure personality. The NEO-FFI Personality Questionnaire was used as the research tool. The study was conducted electronically. Statistical analyses were performed using the Microsoft Excel methods package. Results: The Polish national junior and senior Olympic karate team sportsmen do not differ in personality (their profiles are identical and average level in all dimensions). Likewise, players of the Polish junior and senior handball teams do not differ in personality. However, their profiles are similar - the seniors are distinguished only by a high level of extraversion. Moreover, when comparing the personality of Olympic karate juniors and seniors (combat sport) with that of handball juniors and seniors (team sport), no statistically significant differences were found in the raw test results. Conclusions: The researched population of athletes, personality was probability formed at the junior level and remained unchanged at the senior level, apart from motor skills, technical-tactical skills, and sports experience that developed with age. Such a conclusion is valid on the assumption that seniors, when they were juniors, did not differ in personality from the young athletes we studied.